Efficacy of Butylphthalide Soft Capsules Combined with Shuxuetong Injection in the Treatment of Acute Cerebral Infarction. Issue 1 (December 2020) - Zhang, Wentao; Zuo, Ping; Wang, Feng; Cui, Yinglin
Abstract: Objective: To study the clinical effect of butylphthalide soft capsule combined with Shuxuetong injection in the treatment of acute cerebral infarction. Methods: A total of 94 patients with acute cerebral infarction admitted in our hospital from March 2018 to February 2020 were selected and divided into two groups according to the random number table method. The patients in both groups received conventional treatment programs, the control group (n=47) was given Shuxuetong injection, the test group (n=47) was given combination therapy of butylphthalide soft capsules and Shuxuetong injection on the basis of conventional treatment, and compared the efficacy and related indicators of patients in the two groups. Results: The total effective rate of treatment in the test group was 95.74%, which was significantly higher than that in the control group, which was 80.85%; the NIHSS score in the test group was lower than that in the control group, and the ADL score was higher than that in the control group; the complication rate in the test group was 14.89%, which was significantly lower than the control group's 40.43%, the difference between the two groups of data is statistically significant (P < 0.05). Conclusion: For patients with acute cerebral infarction, the use of butylphthalide soft capsules combined with Shuxuetong injection can achieve the desired results, and it has a positive effect on the recovery of nerve function and self-care ability, and it can also reduce the risk of complications. It is a treatment plan that is worth promoting.